Life-Threatening Adverse Events Following Therapeutic Opioid Administration in Adults: Is Pharmacogenetic Analysis Useful?. (2013) - Madadi, Parvaz; Sistonen, Johanna; Silverman, Gregory; Gladdy, Rebecca; Ross, Colin J; Carleton, Bruce C; Carvalho, Jose C; Hayden, Michael R; Koren, Gideon
Abstract : BACKGROUND: Systemic approaches are needed to understand how variations in the genes associated with opioid pharmacokinetics and response can be used to predict patient outcome. The application of pharmacogenetic analysis to two cases of life-threatening opioid-induced respiratory depression is presented. The usefulness of genotyping in the context of these cases is discussed. METHODS: A panel of 20 functional candidate polymorphisms in genes involved in the opioid biotransformation pathway ( CYP2D6, UGT2B7, ABCB1, OPRM1, COMT ) were genotyped in these two patients using commercially available genotyping assays. RESULTS: In case 1, the patient experienced adverse outcomes when administered codeine and morphine, but not hydromorphone. Genetic test results suggested that this differential response may be due to an inherent propensity to generate active metabolites from both codeine and morphine. These active metabolites are not generated with hydromorphone. In case 2, the patient experienced severe respiratory depression during postoperative recovery following standard doses of morphine. The patient was found to carry genetic variations that result in decreased morphine efflux transporter activity at the blood-brain barrier and increased sensitivity to opioids. CONCLUSIONS: Knowledge of the relative contribution of pharmacogenetic biomarkers and their influence on opioid response are continually evolving. Pharmacogenetic analysis, together with clinical history, has the potential to provide mechanistic insight into severe respiratory depressive events in patients who receive opioids at therapeutic doses.